Kaṉṉic caṅku : Tirukkāvalūrk kalampakat tiṟaṉayvu - Antōṉi Kurucu, A., 1950- (Kiṭaikkumiṭaṅkaḷ Toṉ Pōskō Accakam, 1981)
Articles on Constantino Giuseppe Beschi's (Vīramām uṉivar's) Tirukkāvalūr kalampakam, verse work in kalampakam genre, in praise of Aṭaikkala Mātā, form of Virgin Mary, enshrined at Tirukkāvalūr, Tiruchirapalli District, Tamil Nadu.